الألعاب التعليمية عبر الشبكة وردوول wordwall لتعليم مهارة القراءة في نظر الطلا ب - Sa'diyah, Halimatus; Mubasyiroh, Mubasyiroh (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The new paradigm in education has led to the adaptation of learning with technology and digital. As in the learning of reading skills makes adjustments to the changes that occur so that it can be easier for students to read and understand Arabic texts. Wordwall online educational games are used to support the learning of reading skills process at the student level. The learning process gives rise to varied perceptions from each student. Therefore, this study aims to determine and describe student perceptions of the online educational game wordwall in learning of reading skills. This type of research is descriptive qualitative with research instruments questionnaires, interviews and documentation. The research subjects were Psychology students in Ps.2 PKPBA class (Arabic Language Class Program) UIN Maulana Malik Ibrahim Malang for the academic year 2021/2022 held 30 respondents. The results showed that (1) Ps.2 Psychology PKPBA class students were motivated to learn reading skills by using an online educational game wordwall, (2) using an online educational game wordwall to make it easier for students to read and understand the text, and (3) students have been happy and challenged to use wordwall online educational games to do exercises with a limited time.